Research Progress on the Application of Covalent Organic Framework Nanozymes in Analytical Chemistry - Dongmei Yao; Ling Xia; Gongke Li (Biosensors, 2024)
Covalent organic frameworks (COFs) are porous crystals that have high designability and great potential in designing, encapsulating, and immobilizing nanozymes. COF nanozymes have also attracted extensive attention in analyte sensing and detection because of their abundant active sites, high enzyme-carrying capacity, and significantly improved stability. In this paper, we classify COF nanozymes into three types and review their characteristics and advantages. Then, the synthesis methods of these COF nanozymes are introduced, and their performances are compared in a list. Finally, the applications of COF nanozymes in environmental analysis, food analysis, medicine analysis, disease diagnosis, and treatment are reviewed. Furthermore, we also discuss the application prospects of COF nanozymes and the challenges they face.